Antony Deschamps - Elegiac Poet in the Context of National Poetry - V. I. Pinkovsky (Научный диалог)
The question of the place occupied in the history of French poetry by Anthony Deschamps (Antony Deschamps, 1800-1869), a romantic poet almost forgotten already at the end of the 19th century, is examined. Concerning this question, the author of the article turns to the elegy genre leading in the work of Deschamps and in romantic lyrics as a whole establishing the importance of the poet in the context of the history of the French elegy. The relevance of this approach is determined by the fact that insufficient attention is paid to the genre aspect of literary history in French literature of the twentieth and early twenty-first centuries, which affects the full understanding of the significance of those writers whose merits are related to the genre sphere. Since the factor of personal (rather than a priori given genre) lyricism is very important in the romantic elegy, the article pays great attention to the character of A. Deschan, the opinion of his contemporaries. An analysis of Deschan elegy, comparing them with historically preceding examples of the genre, allows us to conclude that Deschan, unlike poets of the 18th - early 19th centuries, did not create a stable elegiac model similar to, for example, the Lamartinian elegy, but on the contrary, brought romantic principle of creative freedom to life. Largely thanks to such authors, not too remarkable, avoiding high-profile declarations and radical acts, important work was done to turn poetry, strictly regulated by genre norms, into modern lyrics, with its many forms that meet the needs of a flexible embodiment of diverse individual feelings.